PAXX, Not NHEJ1 Is an Independent Prognosticator in Colon Cancer - Arora, Mohit; Kumari, Sarita; Singh, Jay; Chopra, Anita; Chauhan, Shyam S. (Frontiers in Molecular Biosciences, 2020)
Classical Non-Homologous End Joining (NHEJ) pathway is the mainstay of cellular response to DNA double strand breaks. While aberrant expression of genes involved in this pathway has been linked with genomic instability and drug resistance in several cancers, limited information is available about its clinical significance in colon cancer. We performed a comprehensive analysis of seven essential genes, including XRCC5, XRCC6, PRKDC, LIG4, XRCC4, NHEJ1 and PAXX of this pathway, in colon cancer using multi-omics datasets, and studied their associations with molecular and clinicopathological features, including age, gender, stage, KRAS mutation, BRAF mutation, microsatellite instability status and promoter DNA methylation in TCGA colon cancer dataset. This analysis revealed upregulation of XRCC5, PRKDC, and PAXX in colon cancer compared to normal colon tissues, while LIG4 and NHEJ1 (XLF) displayed downregulation. The expression of these genes was independent of age and KRAS status, while XRCC5, PRKDC, and LIG4 exhibited reduced expression in BRAF mutant tumors. Interestingly, we observed a strong association between XRCC6, XRCC5, PRKDC and LIG4 overexpression and microsatellite instability status of the tumors. In multivariate analysis, high PAXX expression emerged as an independent prognostic marker for poor overall and disease specific survival. We also observed hypomethylation of PAXX promoter in tumors, which exhibited a strong correlation with its overexpression. Furthermore, PAXX overexpression was also associated with several oncogenic pathways as well as a reduction in numbers of tumor-infiltrating lymphocytes.